Classroom Practices and Academic Outcomes in Urban Afterschool Programs: Alleviating Social-Behavioral Risk. (March 2018) - Cappella, Elise; Hwang, Sophia H. J.; Kieffer, Michael J.; Yates, Miranda
Given the potential of afterschool programs to support youth in urban, low-income communities, we examined the role of afterschool classroom ecology in the academic outcomes of Latino and African American youth with and without social-behavioral risk. Using multireporter methods and multilevel analysis, we find that positive classroom ecology (i.e., social dynamics, responsive instruction, and organized management) positively predicted academic skills and self-concept across 1 year. For academic skills, the association was magnified for students with social-behavioral difficulties; for academic self-concept, the association was magnified for students without social-behavioral difficulties. No significant relation was found between fall classroom ecology and spring academic engagement; yet in classrooms with more positive ecology, youth with initial social-behavioral risk were more academically engaged. Results suggest the need to consider the role of afterschool classrooms and instructors in promoting supportive interactions and advancing academic outcomes for youth facing distal and proximal risk at the transition to adolescence.